Análise do trabalho em altura de uma obra pública na cidade de Martins-RN - Costa, Felipe Dacio (Universidade Federal Rural do Semi-Árido, 2018)
Studying Safety is a factor of great importance for the well-being of the economically active Brazilian population. In particular, civil construction is a procedure of the type with high rates of accidents at work. The Construction Industry (CI) has a high volume of activities related to work at heights, and these are those with the second highest rate of mortality at work. The Ministry of Labor and Employment (MTE) determines the preventive measures, through the Regulatory Norms (NR), the companies that are favorable to working conditions and, consequently, avoiding that the exchange processes are more employed. NR 35 (Work at Height) is a market that is subject to a large number of employees, it also requires minimum conditions so that work at heights can be carried out for the purpose of working at high altitude accidents. The research was carried out within the scope of NR 35 in a public construction work in the city of Martins / RN, through technical visits and applications of questionnaires. There were several irregularities in the use of Personal Protective Equipment (PPE) in collective protection systems, both in the peripheries of the structure with movements, in general, practically all security media were inadequate, or not risks to the health and well-being of the worker.
Monografia
Keywords: Construção civil.; Acidentes de trabalho; Segurança do trabalho; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA